Project-based blended learning for vocational education: Enhancing digital marketing competencies and team spirit - Tan, Linxi; Ratanaolarn, Thanin; Sriwisathiyakun, Kanyarat (My University, 2025)
Developing digital marketing competencies and team spirit is essential in vocational education to cope with the digital economy’s demands. Based on the needs assessment of vocational students and related literature research, this study discusses how to develop and implement the project-based Blended Learning (PjBBL) model and evaluates its effectiveness in enhancing digital marketing competencies and team spirit among vocational students. The research employs a quasi-experimental design with 90 students from Tongren Polytechnic College, Guizhou, China, divided equally into experimental and control groups. The experimental group followed the PjBBL model. The control group used blended learning (BL) methods. The learning activity lasted 8 weeks, pre-tests and post-tests were administered using a 5-point Likert scale for digital marketing competencies and team spirit. MANOVA analysis (level 0.05) showed a significant difference in digital marketing competencies and team spirit between PjBBL and BL. The results revealed that while both groups showed improvement, the experimental group achieved significantly higher scores in both areas, indicating the effectiveness of the PjBBL model. This study provides valuable insights into improving vocational education through innovative teaching approaches.
Keywords: Classroom Practice; Curriculum Studies; digital marketing competencies; Higher Education; Project-based blended learning; team spirit; vocational education